Approaches to the Identification of the Boundaries of Spatial Networks as Multidimensional Territorial Socio-economic Systems - Mikhaylov, Andrey S. (International Journal of Economics and Financial Issues, 2016)
Contemporary socio-economic space is based on spatial networking of a wide range of actors involved in the process of co-creation of value. These interactions expressed in entrepreneurial ‘co-opetition’, interpersonal relations, territorial embeddedness, reflect a certain degree of proximity among its members. Different configurations of participants and their networking generate a variety of forms being conceptualized, such as the industrial district, technopolis, cluster, etc. Objective desire of the state authorities and other stakeholders to reproduce the best practice imprinted in these concepts triggers the development of respective state support programs, focused on the development of existing nodes. In this context it is especially important to develop a mechanism of identifying the attributes and the territorial boundaries of whatever type of spatial networking implied. The article clarifies the concept of the boundaries of spatial networking based on an interdisciplinary approach, involving consideration of a number of factors (spatial, temporal, institutional, social, cognitive, etc.). The types of boundaries of the spatial networking and a description of their basic properties are identified. Keywords: spatial community, territorial community, territorial socio-economic system, region, interaction boundaries, proximity, commonality, spatial networking JEL Classifications: L220; R120; R320